Transitions to long-term unemployment risk among young people: Evidence from Ireland - Elish Kelly; Seamus McGuinness; Philip J. O'Connell (The Economic and Social Research Institute (ESRI), 2011)
Many young people have short spells of unemployment during their transition from school to work; however, some often get trapped in unemployment and risk becoming long-term unemployed (OECD, 2009). Much research has been undertaken on the factors that influence unemployment risk for young people during their school-to-work transition. However, very little is known about the factors associated with long-term unemployment risk for those youths that become unemployed. This paper attempts to fill this gap in the literature by identifying the characteristics associated with young peoples' long-term unemployment risk in Ireland. The research, which is conducted using multivariate statistical analysis, uses a combination of unemployment register data and information gathered from a specially designed claimant questionnaire that was issued to all jobseekers making an unemployment benefit claim between September and December 2006. The results indicate that factors such as a recent history of long-term unemployment, a lack of basic literacy/numeracy skills and low levels of educational attainment, all have a significant impact on the likelihood that young people will remain unemployed for 12 months or more. A number of attributes are gender specific, such as the presence of children, additional welfare benefits and spousal earnings for females, and apprenticeship training and participation in a public sector job creation scheme for males. Comparisons with the characteristics associated with older welfare claimants long-term unemployment risk, reveal some interesting difference between younger and older unemployed individuals.
Keywords: 330; youth unemployment; long-term unemployment risk; Ireland